Regional cryosphere strategy for the Hindu Kush Himalaya - Sher Muhammad; Mohd. Farooq Azam; Miriam Jackson; Qianggong Zhang (Journal of Mountain Science, 2026)
The Hindu Kush Himalaya (HKH) hosts the largest concentration of glaciers, seasonal snow, and permafrost outside the polar regions. Ongoing climate change has accelerated glacier mass loss, reduced snow cover, degraded permafrost, and altered runoff seasonality. These changes have amplified multihazard risks such as glacial lake outburst floods, avalanches, and landslides, with cascading impacts on water, energy, food, ecosystems, and livelihoods. Yet, field monitoring remains sparse, fragmented, and uneven across the region with limited long-term records and minimal data sharing. This perspective presents a Regional Cryosphere Strategy (RCS) for the HKH that responds to these deficits by: (i) consolidating and institutionalising standardised monitoring of glaciers, snow, and permafrost; (ii) building sustained capacity through specialised regional capacity-building activities, fellowships, and shared instrumentation with priority given to a Gender Equality and Social Inclusion (GESI) framework; (iii) establishing a Regional HKH CryoHub to ensure Findable, Accessible, Interoperable, and Reusable (FAIR) and policy-relevant data and knowledge services; and (iv) prioritising operational decision-support services such as the HKH seasonal Snow Watch for water and energy planning, hazard monitoring and early warning systems, and basin-scale assessments that link cryosphere trends to risks for people and infrastructure. This strategy is designed to align HKH observations and services with global initiatives, ensuring that regional data streams inform global assessments while countries can access technical and financial support mechanisms. We argue that a basin-representative, quality-assured, and interoperable cryosphere observation and services system can strengthen regional resilience, reduce risks, and amplify the HKH voice in global climate dialogues.